If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (42 + 2x) = (3x + 4) Remove parenthesis around (42 + 2x) 42 + 2x = (3x + 4) Reorder the terms: 42 + 2x = (4 + 3x) Remove parenthesis around (4 + 3x) 42 + 2x = 4 + 3x Solving 42 + 2x = 4 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 42 + 2x + -3x = 4 + 3x + -3x Combine like terms: 2x + -3x = -1x 42 + -1x = 4 + 3x + -3x Combine like terms: 3x + -3x = 0 42 + -1x = 4 + 0 42 + -1x = 4 Add '-42' to each side of the equation. 42 + -42 + -1x = 4 + -42 Combine like terms: 42 + -42 = 0 0 + -1x = 4 + -42 -1x = 4 + -42 Combine like terms: 4 + -42 = -38 -1x = -38 Divide each side by '-1'. x = 38 Simplifying x = 38
| 2(10.4)+3y=24 | | -2(y-3)=-6y-12+2y | | 3a+12a=-7 | | 7.5a+9.2-6.8a-11b= | | -6(-1-3x)=-120 | | 9x^3+54x^2= | | 9x+3x=24 | | 4(2y-10)=3(2y+8) | | 3(5x+1)-2=3y+6 | | -2(y-3)=-6y-12+12y | | 4x-9y+3x= | | 3(y-10)+1=-5.5(y-8) | | X^2-5-35=0 | | -9(x-6)-4=50 | | -10x=-27x-17 | | x+3(1.25)=7.25 | | (4a-3b)(2a+6b)= | | 5xt-3xy= | | h(-0.5)=-4.5+3 | | y+.6=.8(y+2) | | y+.6=.8(y+2) | | Y=2b^2+4+9b | | [4x]=18+7y | | 2.3w+7+8.1+3w= | | 4.25*16= | | 10(2-m)-5(1-3m)=30 | | 0.53+0.34t=3.44t-0.71 | | 4y+16x=32 | | 0.53+0.34t=3.44t-0.71 | | 10(2-m)-5(1-3m)=30 | | 30+4n=95 | | 114=-6(2x-7) |